The archaeology of early colonial Manila a hybrid city in global history - Hsieh, Ellen (University Press of Florida, 2025)
This book uses archaeological, historical, and ethnographic resources to document the ways Manila was transformed by the arrival of Spanish colonists in 1571 and how the city in turn shaped the modern world"--